2022
DOI: 10.3389/fnmol.2022.938280
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in local activity and functional connectivity in patients with postherpetic neuralgia after short-term spinal cord stimulation

Abstract: IntroductionThe efficacy of short-term spinal cord stimulation (stSCS) as a treatment for neuropathic pain in patients with postherpetic neuralgia (PHN) has already been validated. However, the potential alterations in brain functionality that are induced by such treatment have yet to be completely elucidated.MethodsThis study use resting-state functional magnetic resonance imaging (rs-fMRI) to detect the changes in regional homogeneity (ReHo) and degree centrality (DC) related to stimulator-induced pain relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…In a 99 mTc-ECD SPECT/CT brain imaging study, the RO blood ow was altered in the anxiety disorder group compared with that in the healthy control group (Zhuang et al, 2015). Additionally, a study of the PHN showed a signi cant correlation between degree centrality changes in the RO and changes in pain, emotion, and sleep quality (Fan et al, 2022). In our study, increased fALFF values of the right RO were found in the HZ-RP with HA group compared with those of the HZ-RP with LA group, and the VAS and SAS scores contributed to explaining the variance in the brain region.…”
Section: Discussionsupporting
confidence: 64%
“…In a 99 mTc-ECD SPECT/CT brain imaging study, the RO blood ow was altered in the anxiety disorder group compared with that in the healthy control group (Zhuang et al, 2015). Additionally, a study of the PHN showed a signi cant correlation between degree centrality changes in the RO and changes in pain, emotion, and sleep quality (Fan et al, 2022). In our study, increased fALFF values of the right RO were found in the HZ-RP with HA group compared with those of the HZ-RP with LA group, and the VAS and SAS scores contributed to explaining the variance in the brain region.…”
Section: Discussionsupporting
confidence: 64%
“…A brain structure study via experimental induction of low back pain found that asymptomatic participants had greater grey matter density at MOG_L than participants with pain [ 48 ]. A study on alterations in local activity and functional connectivity in patients with postherpetic neuralgia after short-term spinal cord stimulation found patients with increased ReHo values at the MOG [ 49 ]. The visual system plays a prominent role in migraine, especially migraine with aura [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism underlying PHN is immune activation, whereby the immune system produces cytokines and other inflammatory molecules that can damage nerve cells and lead to persistent pain. Furthermore, chronic inflammation can alter the way pain signals are processed in the central nervous system, thereby allowing pain to persist even after the initial injury has healed ( 47 , 49 , 50 ). Lastly, genetic factors may also influence the development of PHN.…”
Section: Discussionmentioning
confidence: 99%